2004
DOI: 10.2527/2004.8251499x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing weaning age improves pig performance in a multisite production system1

Abstract: Two trials were conducted to determine the effects of weaning age on pig performance in a multisite production system. The second trial also evaluated the effects of modifying the nursery feeding program according to weaning age. In Trial 1 (2,272 pigs), treatments included weaning litters at 12, 15, 18, or 21 d of age. In Trial 2 (3,456 pigs), litters were weaned at 15, 16, 18, 19, 21, or 22 d of age and categorized into three treatments (15.5, 18.5, or 21.5 d of age). In Trial 2, pigs in each age group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
89
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 10 publications
10
89
5
2
Order By: Relevance
“…Main et al (2004) reported similar findings for increased weaning age. Davis et al (2006) also reported increased nursery mortality of pigs weaned at younger ages and attributed this effect to an unfavorable impact on immunity.…”
Section: Nursery and Finishing Mortalitysupporting
confidence: 83%
“…Main et al (2004) reported similar findings for increased weaning age. Davis et al (2006) also reported increased nursery mortality of pigs weaned at younger ages and attributed this effect to an unfavorable impact on immunity.…”
Section: Nursery and Finishing Mortalitysupporting
confidence: 83%
“…feeding behaviour or intake after weaning (Gonyou et al, 1998;Worobec et al, 1999;Main et al, 2004). Low energy intake at weaning is the most important factor affecting small intestine villous height of piglets after weaning (Marion et al, 2002), and has known negative effects on the piglets' metabolism, growth and health (Le Dividich and Sè ve, 2000;Dong and Pluske, 2007), thus being a major welfare issue.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were carried out on eight infant domestic pigs (mini-Hanford strain), each ten to thirty days old, and six juvenile minipigs (three Göttingen strain and three mini-Hanford strain), each two to three months old. Infant pigs wean between 14 and 28 days old (Dritz et al, 1996;Main et al, 2004;Davis et al, 2006).…”
Section: Methodsmentioning
confidence: 99%